Weighting Model of Internal Rating System to Control Non-Performing Loan at. PT. XYZ (Persero) Tbk - Aripradipta, Nieken Sukma; Wiryono, Sudarso Kaderi (The Indonesian Journal of Business Administration, 2012)
The effectiveness and the efficiency of controlling and managing credit is become the most important things that need to be considered in bank, due to the function of bank as an intermediation in collecting and disbursement of people money and credit become the largest source of income for the corresponding bank. PT. XYZ (persero) Tbk is the fourth largest bank in Indonesia. As one financial institution that plays an important role in the economical sector of Indonesia, XYZ has to maintain the stability of their performance. In maintaining the stability of their performance, PT. XYZ (Persero) Tbk is completed with a tools called as Internal Rating System (IRS) that could help them in analyzing the feasibility of the potential debtor for the credit approval. However, as the economy fluctuation in Indonesia, PT. XYZ (Persero) Tbk faces a problem related with the increment of the NPL (Non-Performing Loan). It is due to the errors of the company in determining the weighted value in IRS. Where they were giving the same weighting value for a different economical sectors, in fact each economical sector are having a different risk and characteristics. This research would give a proposed solution for PT. XYZ (Persero) Tbk as alternative solution that is new weighting model for IRS by considering the characteristics and risks for each economical sector. Where the implementation of this new weighting model hopefully could help PT. XYZ (Persero) Tbk in controlling their NPL ratios. Key Words: Risk Management, Internal Rating System, IRS, weighting model, banking, credit.